198 IFN-kinoid in systemic lupus erythematosus (SLE): results from a phase 2b, randomized, placebo-controlled study. (April 2019) - Houssiau, Frédéric; Thanou, Aikaterini; Mazur, Minodora; Ramiterre, Edgar; Gomez Mora, Danny Alexis; Misterska-skora, Maria; Campos, Risto Perich; Smakotina, Svetlana Anatolyevna; Cruz, Sergio Cerpa; Louzir, Bassem; Camille, Therese; Tee, Michael
Abstract : Background: The immunotherapeutic vaccine Interferon--kinoid (IFN-K) consists of a heterocomplex of inactivated recombinant human IFN-2b coupled to a T-helper carrier protein, Keyhole Limpet Haemocyanin. A phase I/IIa was published. Here, we report the results of a 36 week (w) phase 2b, randomized, double-blind, placebo-controlled (PBO), multi-center study assessing the efficacy and safety of IFN-K in patients with active SLE on standard of care therapy. Methods: SLE patients (4 ACR criteria) with moderate to severe disease activity (SLEDAI 2K 6 and 1 BILAG A and/or 2 BILAG B scores); positive IFN gene signature; and ANA and/or anti-dsDNA, were randomized (1:1) to 5 IM injections of IFN-K or PBO at days 0, 7, 28, and months 3 and 6. Co-primary objectives at w36 were neutralization of IFN gene signature and BICLA response modified by mandatory corticosteroid (CS) tapering (5 mg/d prednisolone equivalent) by w24 with no increase to w36. Secondary objectives at w36 were SRI(4) and SRI(4) with CS tapering (5 mg or 7.5 mg/d prednisolone equivalent) by w36, Lupus Low Disease Activity State (LLDAS), safety and immunogenicity. Results: Among 185 patients randomized, 91 and 93 were respectively treated with IFN-K and PBO, and 85 (92.4%) and 84 (90.3%) completed the study. Seventy-two of 79 (91.1%) IFN-K treated patients (Per Protocol Set) developed anti-IFN neutralizing antibodies (Abs). Primary and secondary outcome measures at w36 are detailed in the Table: IFN-K was well tolerated, with similar rates of treatment-emergent adverse events (TEAEs 82.4% vs 76.3%) and TEAEs leading to study drug discontinuation (4.4% vs. 4.3%) in the IFN-K and PBO groups, respectively. Serious adverse events (SAEs) were more common on PBO vs IFN-K (12.9% vs 6.6%). Cancer (n=4) and lupus nephritis (n=2) were reported in the PBO group and there was one severe infection in the IFN-K group. One death occurred in each group. Conclusions: IFN-K induced neutralizing anti-IFN Abs in 91.1% of treated patients and significantly reduced IFN gene signature. Modified BICLA at w36 did not differ between IFN-K and PBO. Trends on SRI (4) with steroid tapering at w36 favored IFN-K, and became significant when patients exhibiting neutralizing Abs were included in the exploratory analysis. Furthermore achieving a Lupus Low Disease Activity State discriminated the two groups at w36, in favor of IFN-K. A significant CS sparing effect of IFN-K was observed from w28 onwards. The safety profile of IFN-K was acceptable. Results merit further evaluation in phase 3 studies. Funding Source(s): The study was funded by Neovacs.